Iterative Frequency-Domain Packet Combining Techniques for UWB Systems with Strong Interference Levels - Silva, Mário Marques da (2015)
UWB (Ultra Wideband) systems tend to suffer strong interference from signals that occupy a significant part of the transmission band. This is an important constraint, especially when the channel remains fixed for a long period of time. In order to overcome this limitation, this paper considers UWB systems employing Single-Carrier with Frequency-Domain Equalization techniques. We propose the corresponding receiver, which also allows the soft packet combining associated to different Automatic Repeat ReQuest transmission attempts, as a measure to improve the performance through the exploitation of diversity. Our techniques are able to cope with strong interference levels as well as deep fading, even for fixed channels.